2005
DOI: 10.1007/s10545-006-0290-3
|View full text |Cite
|
Sign up to set email alerts
|

Anaplerotic diet therapy in inherited metabolic disease: Therapeutic potential

Abstract: Beginning with phenylketonuria, dietary therapy for inborn errors has focused primarily on the restriction of the precursor to an affected catabolic pathway in an attempt to limit the production of potential toxins. Anaplerotic therapy is based on the concept that there may exist an energy deficit in these diseases that might be improved by providing alternative substrate for both the citric acid cycle (CAC) and the electron transport chain for enhanced ATP production. This article focuses on this basic proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
131
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 23 publications
(20 reference statements)
5
131
0
Order By: Relevance
“…Low C10 MCT is recommended due to the evidence that C10 fats require CACT for oxidation (Rubio-Gozalbo et al 2004). Some cases with long-chain FAO disorders (LCHAD, VLCAD, CPT1, CPT2, and CACT) have been treated with triheptanoin, a fatty acid with seven carbon acids, with good results, especially with respect to myocardiopathy and hypoglycemia (Roe and Mochel 2006). The essential fatty acids linoleic acid (3-4%) and linolenic acid (0.5-1%) should be provided, in a ratio from 5:1 to 10:1, with walnut, canola, linseed, sunflower, wheat germ, or soy oil; this has been used with our patients (Spiekerkoetter et al 2009).…”
Section: Dietary Treatment and Monitoringmentioning
confidence: 99%
“…Low C10 MCT is recommended due to the evidence that C10 fats require CACT for oxidation (Rubio-Gozalbo et al 2004). Some cases with long-chain FAO disorders (LCHAD, VLCAD, CPT1, CPT2, and CACT) have been treated with triheptanoin, a fatty acid with seven carbon acids, with good results, especially with respect to myocardiopathy and hypoglycemia (Roe and Mochel 2006). The essential fatty acids linoleic acid (3-4%) and linolenic acid (0.5-1%) should be provided, in a ratio from 5:1 to 10:1, with walnut, canola, linseed, sunflower, wheat germ, or soy oil; this has been used with our patients (Spiekerkoetter et al 2009).…”
Section: Dietary Treatment and Monitoringmentioning
confidence: 99%
“…Mass isotopomers of 13 C-glucose in plasma. Plasma 13 Cglucose was enriched from [5,6,[7][8][9][10][11][12][13] C 3 ]heptanoate in both normal and mutant (glucose transporter type I deficiency, G1D) animal groups. Data were corrected for the natural abundance of 13 C. Glucose was mostly enriched in M ĂŸ 2 (Control: 4.63%±1.5%; G1D: 5.28%±1.22%) and M ĂŸ 3 (Control: 3.65%±0.86%; G1D: 3.45%±0.69%).…”
Section: C-nuclear Magnetic Resonance Spectramentioning
confidence: 99%
“…[9][10][11] Triheptanoin has been previously used in disorders of mitochondrial fat oxidation, glycogen storage, and pyruvate metabolism. 10,12 Additionally, it has been reported that heptanoate derived from triheptanoic diet may exert anticonvulsant effects in epileptic animal models while refilling depleted brain TCA cycle intermediates. 11 As illustrated in Figure 1, the standard, whole-organ notion that explains these findings is that dietary triheptanoin is metabolized to plasma heptanoate and C5 ketones (b-ketopentanoate and b-hydroxypentanoate), 10 both of which can enter the TCA cycle at the level of acetyl-CoA and propionyl-CoA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations